Applying Collaborative Strategic Reading Strategy in Improving Reading Comprehension Achievement of 7th Grade Students at Buddhis Bodhicitta School - Tantry, Wednie Aprillia; Ganie, Rohani; Putri, Liza Amalia (LingPoet: Journal of Linguistics and Literary Research, 2021)
This study attempts to explore the application of collaborative strategic reading strategy in improving reading comprehension achievement of 7th grade students at Buddhis Bodhicitta School and difficulties faced by the students in learning it. The methodology used in this research is Classroom Action Research (CAR). The data of this research are the result of reading tests taken from pre-test I & II and supported by the results of the questionnaires. The subjects of the research are forty-four students of the seventh grade of Buddhis Bodhicitta School. The findings of the research are the mean of pre-test I is 54,3 and the mean of post-test I is 70,2, the mean of pre-test II is 73,6 and the mean of post-test II is 75. It is concluded that using collaborative strategic reading can improve students’ achievement in reading comprehension. Then, there are some difficulties faced by the students in learning reading comprehension such as difficult to get the point of the text in preview strategy, did not know the meaning of difficult words, wrote the text by using their own words, did not know how to wrap up the text, difficult to work in a group, and could not follow the instruction.